The Coptic Magical Papyri Project: Progress Report - Dosoo, Korshi (Journal of Coptic studies, 2022)
For three years, The Coptic Magical Papyri project based at the Julius-Maximilians-Universität Würzburg has been working to advance the study of the corpus of magical texts written in the Coptic language. This article provides a survey of some of its findings to date, introducing the history of the study of Coptic magical texts before describing the corpus of over 500 manuscripts in terms of its contents, and its temporal, geographic, material, and linguistic features.